A Comparative Clinical Evaluation on the Efficacy of Kuberaksha & Yava with Lifestyle Modification, in The Management of Prameha with Special Reference to Prediabetes (International Journal of Ayurveda and Pharma Research, 2021)
We are living in the age of complexity, contradiction, and challenge relating to various health issues such as lifestyle disorder, ageing, mental health euthanasia, drug resistance and so on. Diabetes Mellitus is a Giant disease and major health issue that has reached alarming level in spite of terrific advance in modern medical science. Prediabetes is the precursor stage before Diabetes Mellitus, in which not all of the symptoms required to diagnose diabetes are present, but blood sugar is abnormally high. Prediabetic persons are considered to be at increased risk for the subsequent development Diabetes Mellitus. Sushruta Samhita mentioned, all varieties of Prameha if not treated at appropriate time, become changed to Madhumeha which is incurable. So, early detection, treatment and prevention of this disease in Prediabetic stage is needed. The modification of lifestyle should be the first aim and objectives to restrict or combat such problems, beside this prime objective, some medication which is safe and efficacious to be introduced. So, a clinical study with 60 patients has been conducted on Prediabetes through the management with ‘Kuberaksha’ and ‘Yava’ in such 2 groups of treatment. The two drugs are carrying such properties which acts in Samprapti vighatana (prevent pathogenesis) of the disease. In both cases statistically significant results are found (P